Selective Colorimetric Detection of Nitrite in Water using Chitosan Stabilized Gold Nanoparticles Decorated Reduced Graphene oxide - Amanulla, Baishnisha (Sci Rep, 2017)
Excess nitrite (NO(2) (-)) concentrations in water supplies is considered detrimental to the environment and human health, and is associated with incidence of stomach cancer. In this work, the authors describe a nitrite detection system based on the synthesis of gold nanoparticles (AuNPs) on reduced graphene oxide (rGO) using an aqueous solution of chitosan and succinic acid. The AuNPs-rGO nanocomposite was confirmed by different physicochemical characterization methods including transmission electron microscopy, elemental analysis, X-ray diffraction, UV-visible (UV-vis) and Fourier transform infrared spectroscopy. The AuNPs-rGO nanocomposite was applicable to the sensitive and selective detection of NO(2) (−) with increasing concentrations quantifiable by UV–vis spectroscopy and obvious to the naked eye. The color of the AuNPs-rGO nanocomposite changes from wine red to purple with the addition of different concertation of NO(2) (−). Therefore, nitrite ion concentrations can be quantitatively detected using AuNPs-rGO sensor with UV-vis spectroscopy and estimated with the naked eye. The sensor is able to detect NO(2) (−) in a linear response ranging from 1 to 20 μM with a detection limit of 0.1 μM by spectrophotometric method. The as-prepared AuNPs-rGO nanocomposite shows appropriate selectivity towards NO(2) (−) in the presence of potentially interfering metal anions.